The Reliability of Measurements for Tibial Torsion: A Comparison of CT, MRI, Biplanar Radiography, and 3D Reconstructions With and Without Standardized Measurement Training: Original Research - Edmonds, Eric W.; Parvaresh, Kevin C.; Price, Mason J.; Farnsworth, Christine L.; Bomar, James D.; Hughes, Jessica L.; Upasani, Vidyadhar V. (Journal of the Pediatric Orthopaedic Society of North America, 2023)
Background: Accurate and reliable assessment of tibial torsional is critical for the identification and treatment of tibial rotation malalignment, however the ideal rotational measurement modality and technique are controversial. This study compares rotational measurements between computed tomography (CT), magnetic resonance imaging (MRI), biplanar erect radiograph (BER) reconstructions and three-dimensional (3D) reconstructed CT before and after standardized training to evaluate measurement reliability. Methods: Eight adult cadaveric specimens underwent CT, MRI, and BER imaging. Tibial torsion was measured by three independent observers (one resident and two experienced orthopedic surgeons) both before and after standardized measurement instruction. Reliability for inter-observer measurement was evaluated using the Intraclass Correlation Coefficient (ICC). Measurement values for CT, MRI, and BER reconstructions were compared to 3D CT reconstructions analyzed using custom software to align and measure tibial torsion (used as the reference standard). Results: Before training, there was poor inter-observer reliability for CT (ICC=0.492, p=0.014) and moderate inter-observer reliability for MRI (ICC=0.633, p=0.002). There was no inter-method reliability between 3D CT and MRI for 2 of the 3 surgeons, and moderate to good reliability between 3D CT and CT. After training, the inter-observer reliability for CT improved to 0.536 and the inter-observer reliability for MRI improved to 0.701. The BER measurements (no observer involvement) had moderate reliability compared to the 3D CT reconstructions (ICC=0.69, p = 0.026). Measurement error was 4˚ for CT pre- training and 7˚ post- training), and 7˚ for MRI pre-training and 8˚ post-training. Conclusions: A standardized training regimen for MRI measurements improved both inter-observer and intra-observer reliability. Inter-method reliability between CT, MRI and BER compared to reference 3D CT reconstructions demonstrated that all imaging modalities are a valid means to measure tibial rotation, but that they differ in reliability from moderate to good. When assessing tibial torsional deformities, it is important to consider these variations from true rotation and feel comfortable using them for pre-operative planning purposes.